Problematika Kurikulum Merdeka Belajar dalam Pembelajaran PAI di SMK Negeri 1 Rejang Lebong - Maslakha (Yayasan Darusssalam Bengkulu, 2025)
The aim of this research is to identify independent curriculum problems in PAI learning. This research uses a qualitative descriptive method. The techniques used by researchers in collecting data include observation, interviews and documentation. The data sources used are primary and secondary data. Data validity techniques in this research were checked through triangulation, member checking, increased persistence, and peer discussion. Based on research findings by SMKN 1 Rejang Lebong, it can be concluded that PAI teachers face several problems, such as: 1) When planning lessons, problems arise related to limited choices, for example. concentration at school, limited study time in class, and extensive and detailed study material. In the learning process, teachers usually only use printed PAI materials as their teaching media, and also have difficulty creating teaching modules. 2) When implementing teaching materials, teacher creativity decreases, because the only learning method used by teachers in the learning process is the old teaching style, namely lectures and questions and answers. This is influenced by the age factor, and teachers who have worked for many years find it difficult to keep up with existing developments, which affects their skills. 3) In the learning assessment process, teachers pay more attention to assessing children's psychomotor abilities, especially the ability to read the Koran and memorize hadith. This creates problems because assessment activities need to be carried out comprehensively based on the child's cognitive, emotional and psychomotor aspects.